Association of objectively measured physical fitness with health-related quality of life of mid-life women: the FLAMENCO project. (4th May 2021) - Ruiz-Montero, P. J.; Marín-Jiménez, N.; Borges-Cosic, M.; Aparicio, V. A.
Abstract: Objectives: This study aimed to explore the association of physical fitness with health-related quality of life (HRQoL) in mid-life women and to examine the potential independent association of physical fitness components with the physical and mental components from the 36-Item Short-Form Health Survey (SF-36) in this population. Methods: This cross-sectional study comprised 183 mid-life women from southern Spain who participated in the FLAMENCO project. Body composition was measured through an impedanciometer, a stadiometer, and dual-energy X-ray absorptiometry. Physical fitness was objectively measured with the Senior Fitness Test battery (cardiorespiratory fitness, flexibility, and dynamic balance/agility) plus handgrip strength (muscle strength). The SF-36 questionnaire was used to assess HRQoL of the participants. Results: All the physical fitness components were associated with the SF-36 physical function (all p  < 0.05) except for lower-body flexibility. The rest of the physical fitness components showed associations with most of the SF-36 dimensions (all p  < 0.05). Dynamic balance/agility and upper-body flexibility were independently associated with the SF-36 physical component scale, explaining 15% and 17% of the SF-36 physical component scale, respectively. Any physical fitness component showed independent associations with the SF-36 mental component scale. Conclusions: Greater physical fitness levels are associated with better HRQoL of mid-life women. Dynamic balance/agility and upper-body flexibility were the strongest independent physical fitness components associated with the SF-36 physical component scale.